A Longitudinal Study of the Relations Between Theory of Mind, Executive Function, and Lying in Children - Zhao, Changzhi; Shang, Siyuan; Compton, Alison M.; Fu, Genyue; Sai, Liyang (Frontiers in Psychology, 2021)
This study used longitudinal cross-lagged modeling to examine the contribution of theory of mind (ToM), executive function (EF) to children’s lying development and of children’s lying to ToM and EF development. Ninety-seven Chinese children (initial Mage = 46 months, 47 boys) were tested three times approximately 4 months apart. Results showed that the diverse desire understanding and knowledge access understanding components of ToM, as well as the inhibitory control component of EF predicted development of children’s lying, while the diverse belief understanding and false belief understanding components of ToM, and the working memory component of EF did not predict development of children’s lying. Meanwhile, children’s lying predicted development of children’s belief-emotion understanding components of ToM, but not any other ToM components, or EF components. These findings provide longitudinal evidence for the relation between ToM, EF and children’s lying during the preschool years.